1999
DOI: 10.1002/(sici)1096-8628(19990604)84:4<334::aid-ajmg5>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Gaucher disease presenting with extensive mandibular lytic lesions: Identification and expression of a novel acid ?-glucosidase mutation

Abstract: The finding of extensive lytic lesions in the mandible of a 19-year-old Ashkenazi Jewish woman led to the diagnosis of Type 1 Gaucher disease. She had extensive skeletal involvement, marked hepatosplenomegaly, and deficient acid beta-glucosidase activity. Mutation analysis identified heteroallelism for acid beta-glucosidase mutations N370S and P401L, the latter being a novel missense mutation in exon 9. Expression of the P401L allele resulted in an enzyme with a reduced catalytic activity (specific activity ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In a literature review, the rate of cortical loss in the MC was reported as 56.7%, and the inferior displacement of the MC as 18.9% [22]. In the study, the effacement of the borders of the MC was detected in 9 (56.3%) panoramic images and in 7 (43.8%) CBCT images, which our findings showed results consistent with many studies in the literature [13,15,20,22,23,26,48]. Inferior displacement of the MC, on the other hand, was observed in only 1 (6.3%) patient in both panoramic and CBCT images.…”
Section: Discussionsupporting
confidence: 89%
“…In a literature review, the rate of cortical loss in the MC was reported as 56.7%, and the inferior displacement of the MC as 18.9% [22]. In the study, the effacement of the borders of the MC was detected in 9 (56.3%) panoramic images and in 7 (43.8%) CBCT images, which our findings showed results consistent with many studies in the literature [13,15,20,22,23,26,48]. Inferior displacement of the MC, on the other hand, was observed in only 1 (6.3%) patient in both panoramic and CBCT images.…”
Section: Discussionsupporting
confidence: 89%
“…Serious problems such as osteomyelitis may occur because of trabecular bone loss in the mandible. Because of the decreased blood flow, the sensitivity of the bone to infection may increase with GD (27,28). In addition, a risk of pathological fracture exists in areas where trabeculae are weakened.…”
Section: Discussionmentioning
confidence: 99%
“…Neither child was splenectomized. While osteolytic lesions are described in GD, most are large, expanding intramedullary lesions that grow to occupy the entire corticomedullary region of the bone(4)(5)(6). In contrast, the lesions in these two cases demonstrate predominant cortical scalloping with fairly indolent growth.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal manifestations can include abnormal bone remodeling resulting in the characteristic Erlenmeyer flask deformities, painful bone crises, osteopenia, and an increased frequency of fractures. Osteolytic lesions can also occur, but are rare, and tend to be large expanding intramedullary lesions with cortical thinning (4)(5)(6). …”
Section: Introductionmentioning
confidence: 99%